Efforts to Improve Learning Outcomes Building Flat Side Rooms Through Offline Learning Model - Ramuni A (Eduvest - Journal of Universal Studies, 2021)
This study aims to improve student’s learning outcomes on material Flat Sides Solid Figure using worksheet (LKPD) especially for 8th grade class-A student of SMP N 5 Sanggau. The method used was classroom action research. The subjects in this study were 8th grade class-A students. Data collection techniques used observation, measuring, and documentary studying techniques. The instruments used were written test. Based on the result, there is a significant improvement on student’s learning outcomes. It proved by the improvement numbers of student who passed the exam after 2nd Cycle. Which were improved from Pre-Cycle, 1st Cycle, 2nd Cycle are 34%; 73,08%; 92,30% while the averages are 69; 70,96; and 80,08. It proved that applying offline learning models with LKPD in covid-19 pandemic on mathematic will improved students’ learning outcomes. The learning process was morelively because students have a chance to build their own knowledges based on what they learned..